Nuclide control of structural materials tested in electron irradiation test facility - Bakai, A.S.; Dovbnya, A.N.; Zykov, A.I.; Lavrinenko, S.D.; Myakushko, L.K.; Repikhov, O.A.; Torgovkin, A.V.; Shirokov, B.M.; Shramenko, B.I. (Вопросы атомной науки и техники, 2005)
Samples of different alloys (Hastelloy type) held in the container assembly (CA) were irradiated at the Electron Irradiation Test Facility (EITF) in the melt of zirconium and sodium fluorides at the temperature 650оС. The CA consisted of 16 individual containers made of a carbon-carbon (C-C) composite material (placed under covering shell made of stainless steel). The irradiation was done with electron beam at the energy in the spectrum maximum = 9.6 MeV at Linac-10 high-current accelerator that belongs to “Accelerator R&D Complex” affiliated with NSC KIPT. In order to secure the radiation-safe levels of the activity in further work with the samples, the focus of attention was paid to the analysis of γ-spectra in the remnant activities of the materials under study: Hastelloy type samples and fluoride salts after the irradiation. The dynamics was studied of decreasing of the activity levels of EITF components, sample assemblies in the containers being full with fluoride salts and individual samples. Recommendations are issued and measures taken to provide for further radiation-safe work with the irradiated materials. На стенді для радіаційних випробувань проведено опромінення електронами збірки зразків різних сплавів (типу хастелой) в розплаві фторидів цирконію та натрию при температурі 650'С. Збірку складено з 16 окремих контейнерів з вуглець-вуглецевого композиту (в загальній захистній оболонці з нержавіючої сталі). Опромінення проведено пучком електронів з енергією в максимумі спектра близько 9,6 МеВ на сильносрумовому лінійному прискорювачі електронів ЛП-10 НДК «Прискорювач» ННЦ ХФТІ. Для вибору безпечних рівней активності при подальших роботах з зразками особиву увагу приділено аналізу γ-спектрів залишкової активності досліджуваних материалів – зразків сплаву типу хастелой та фторидних солей після опромінення. Досліджено динаміку спаду рівней активності елементів стенду, збірки зразків в контейнерах, які заповнені фторидними солями, та окремих зразків. Дано рекомендації та вжито заходи, що гарантують безпеку при подальших дослідженнях опромінених матеріалів. На стенде для радиационных испытаний проведено облучение сборки образцов различных сплавов (типа хастеллой) в расплаве фторидов циркония и натрия при температуре 650'С, помещенных в 16 отдельных контейнеров из углерод- углеродного композита (в общем защитном кожухе из нержавеющей стали). Облучение проведено пучком электронов с энергией в максимуме спектра = 9,6 МэВ на сильноточном линейном ускорителе электронов ЛУ-10 НИК "Ускоритель" ННЦ ХФТИ. С целью обеспечения безопасных уровней активности при дальнейшей работе с образцами особое внимание уделено анализу характеристик остаточной активности исследуемых материалов – образцов сплава типа хастеллой и фторидных солей после облучения. Измерены уровни активности элементов стенда, сборки образцов в контейнерах, заполненных фторидными солями, и отдельных образцов. Даны рекомендации и приняты меры, обеспечивающие безопасность работы с облученными материалами.